Bone marrow toxicity associated with febantel administration in a dog: Case Report - Petronzio, Abbey; Carabetta, David; Koid, Audrey (Frontiers in Veterinary Science, 2025)
IntroductionThe objective of this case report is to describe a case of bone marrow suppression suspected to be secondary to febantel administration in a dog.Case summaryA 6-year-old neutered male Labrador Retriever was presented for lethargy and fever 15 days after receiving oral febantel. Pancytopenia was noted, and bone marrow sampling was consistent with hypoplasia suspected to be due to the febantel administration as no other toxic insults were identified. The dog made a full recovery in approximately 2 weeks after stopping the febantel.DiscussionThis is the first report of suspected bone marrow toxicity secondary to febantel administration. Febantel is metabolized to fenbendazole, which has been documented as causing bone marrow toxicity in canines.